Companion of the 17th Annual ACM SIGPLAN Conference on Object-Oriented Programming, Systems, Languages, and Applications 2002
DOI: 10.1145/985072.985116
|View full text |Cite
|
Sign up to set email alerts
|

Automatically generating object models from natural language analysis

Abstract: Our goal is to enable rapid production of static and dynamic object models from natural language description of problems. Rapid modeling is achieved through automation of analysis tasks. This automation captures the cognitive schemes analysts use to build their models of the world through the use of a precise methodology. The methodology is based on the use of proposed technique called role posets, and a semi-natural language (called 4W).Original problem statements are automatically translated to 4W language. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The prototype tool Graphic Object Oriented Analysis Laboratory (GOOAL) [40] supports automatic OO modeling and produces static and dynamic models from NL description of user requirements taking decisions sentence by sentence. The underlying methodology of this system includes role posets and semi-natural language (4W).…”
Section: Gooalmentioning
confidence: 99%
“…The prototype tool Graphic Object Oriented Analysis Laboratory (GOOAL) [40] supports automatic OO modeling and produces static and dynamic models from NL description of user requirements taking decisions sentence by sentence. The underlying methodology of this system includes role posets and semi-natural language (4W).…”
Section: Gooalmentioning
confidence: 99%
“…Perez-Gonzalez tried a different approach by presenting a restricted language with a reduced set of words and possible sentences [22]. For this reduced input set they build a tool (GOOAL) capable of generating the corresponding models.…”
Section: A Model From Nlmentioning
confidence: 99%
“…We presented our seminal work at OOPSLA 2002 (Pérez-González & Kalita 2002) showing our initial results with just two simple examples and using just an English version tool. At OOPSLA 2005(Pérez-González et al 2005 we showed our Spanish version tool with an educational approach.…”
Section: Related Workmentioning
confidence: 99%